Frequency tunable continuous THz wave generation in a periodically poled fiber - Liu, Weilin; Zhang, Jiejun; Rioux, Maxime; Viens, Jeff; Messaddeq, Younes [UNESP]; Yao, Jianping (Ieee-inst Electrical Electronics Engineers Inc, 2015)
An all-fiber approach to terahertz generation using a periodically poled optical fiber is proposed and experimentally demonstrated. In the proposed approach, a continuous-wave THz wave is generated at a periodically poled fiber by beating two optical wavelengths from two laser sources with the wavelength spacing corresponding to the frequency of the THz wave. The key component in the system is the periodically poled fiber, which is made by a twin-hole fiber with the fiber core residing between two holes. The twin-hole fiber is then thermally poled at a temperature of similar to 260 degrees C with a voltage of 3.3 kV applied to the silver electrodes inside the two holes to introduce second-order nonlinearity. The quasi phase matching (QPM) condition is achieved by periodically erasing the thermal poling induced second-order nonlinearity with an ultraviolet laser, which enhances the energy conversion efficiency. The proposed approach is validated by an experiment. The emission of a THz wave centered at 3.8 THz with an output power of 0.5 mu W is observed. The frequency tunability between 2.2 and 3.8 THz is also experimentally demonstrated.
Keywords: Difference frequency generation (DFG); Fiber nonlinear optics; Quasi-phase matching (QPM); Second-order nonlinearity; Terahertz (THz); Thermal poling